Investing in suppliers with capacity constraints in a decentralized assembly system. (April 2020) - Fu, Hong; Li, Kai; Fu, Weizhong
Highlights : We develop a model to study the capacity investment problem in an ATO system. We characterize the optimal pricing and production decisions of all chain members. We derive the optimal capacity investment strategy for the assembler. We find that optimal investment may increase in the capacity expansion cost. We show that supply chain operations depends highly on system cost parameters. Abstract: This study investigates a decentralized assembly system, in which a single downstream assembler buys complementary components from multiple upstream suppliers, and then assembles them into a final product to satisfy an uncertain market demand. Suppliers have capacity constraints, and the assembler considers to invest in suppliers to increase their capacities. The investment problem of the assembler is a complex multi-dimensional optimization problem. We first characterize the optimal pricing and production decisions of all supply chain members assuming that the investment strategy is given. We then derive optimal investment strategy for the assembler. We show that the assembler's optimal total investment increases in the retail price, and decreases in both the component production cost and the assembly cost, but is nonmonotonically related to the component capacity expansion cost. We also show that the performance of the entire supply chain highly depends on the allocation of the total component cost between the capacity expansion and production activities.